Trifluomeprazine fed to fattening steers - Koch, B.A.; Smith, E.F.; Richardson, D.; McCarter, M.M. (Kansas Agricultural Experiment Station, 2011)
The steers used in this study were good to choice grade Herefords, averaging 980 pounds, that originated in New Mexico. They had been wintered in central Kansas at a rather high level of feeding. The steers were randomly allotted, according to weight, into four groups of 10 animals each.
Keywords: Beef; Trifluomeprazine; Gain; Carcass data